2016
DOI: 10.4269/ajtmh.15-0828
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Q Fever in New South Wales, Australia: A Case Series (2005–2013)

Abstract: Abstract. Q fever is endemic in Australia, and during the period 2005-2013 our laboratory diagnosed 379 cases in New South Wales. To evaluate clinical symptoms, epidemiology, mode of diagnosis, antibody profiles, and treatment, a subset of 160 (42%) Q fever cases were analyzed in detail following the return of a questionnaire by the patient's doctor and from their laboratory reports. Overall, 82% patients were male and predominantly middle aged. The majority of patients (89%) had animal contact among which 63%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…The majority of research in Australia tends to focus on analysis of notified cases (35), unusual outbreaks, (36, 37), or animal and environmental sources (38). However, a recent study by Bond et al (39) demonstrated the application and outcomes of taking a One Health approach to an outbreak associated with a goat farm.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of research in Australia tends to focus on analysis of notified cases (35), unusual outbreaks, (36, 37), or animal and environmental sources (38). However, a recent study by Bond et al (39) demonstrated the application and outcomes of taking a One Health approach to an outbreak associated with a goat farm.…”
Section: Resultsmentioning
confidence: 99%
“…Q fever is an endemic zoonotic infection in Australia cause by Coxiella burnetii. It has been recognised in other parts of the world, especially among livestock rearing occupations, stock yard and abattoir workers [1][2][3]. Coxiella burnetii can be harboured in most herd and domestic animals including cattle, goats, sheep and dogs, Macropods such as kangaroos and wombats, and also in ticks that are associated with some of these animals [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognised in other parts of the world, especially among livestock rearing occupations, stock yard and abattoir workers [1][2][3]. Coxiella burnetii can be harboured in most herd and domestic animals including cattle, goats, sheep and dogs, Macropods such as kangaroos and wombats, and also in ticks that are associated with some of these animals [2,3]. Coxiella burnetii is particularly concentrated in the placenta, so although it is shed into bodily secretions including faeces, most human infections occur through contact with the placenta of infected animals [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations